Pengaruh Dukungan Sosial Orang Tua, Guru, Teman, dan Self-Efficacy terhadap Grit pada Siswa SMP Boarding School Penghafal Al-Qur’an - Firly Syahira Sihombing; Tarmidi Dadeh; Rahma Fauzia (Lembaga Teewan Journal Solutions, 2026)
Grit is an individual's ability to remain consistent and persistent in achieving long-term goals that are personally important. This study aims to examine the influence of parental, teacher, and peer social support, as well as self-efficacy, on the grit of junior high school students at a Quran memorizing boarding school analyzed through the aspects of consistency of interest and perseverance of effort. The study involved 330 students from Boarding School X in Medan, selected using a total sampling technique. Data were collected using scales measuring grit, parental social support, teacher social support, peer social support, and self-efficacy, all of which had undergone validity and reliability testing. Data analysis was conducted using multiple linear regression. The results indicate significant influences on grit from parental social support (t-value = 10.193, p < 0,05), teacher social support (t-value = 10.679, p < 0,05), peer social support (t-value = 8.624, p < 0,05), and self-efficacy (t-value = 6.107, p < 0,05). Furthermore, the study found that parental, teacher, and peer social support, along with self-efficacy, simultaneously exerted a significant influence on grit (F-calculated = 290.311 > F-table = 2.39; p < 0,05), contributing to 78.1% of the variance.